The Effect of Food Prices on Inflation in the Republic of Serbia - Snežana Radukić; Milan Marković; Milica Radović (Journal of Central Banking Theory and Practice, 2015)
In the Republic of Serbia, food accounts for a significant share in the consumer price index through which the inflation is statistically expressed. Therefore, in considerations of the basic factors of increase in the general price level, a special emphasis is placed on the specific features of the market of agricultural-food products. The aim of this research is to peruse the effect of the characteristics of the food market in Serbia on the inflation rate. High volatility of food prices is present because of the instability of this market, mainly due to seasonal fluctuations of supply and the effect of natural factors. Bearing in mind that the increase in food prices is the main determinant of the increase in the inflation rate, the indirect state control is very important so as to maintain price stability. Special importance is attached to the following instruments of economic policy: commodity reserves, storage policy, and fiscal and foreign trade policy.
Keywords: E31; E58; Q11; 330; food market; volatility of food prices; consumer price index; economic policy; inflation; the Republic of Serbia